Economic burden of stroke in a large county in Sweden - Persson Josefine; Ferraz-Nunes José; Karlberg Ingvar (BMC, 2012)
Abstract Background Stroke remains to be a major burden of disease, often causing death or physical impairment or disability. This paper estimates the economic burden of stroke in a large county of 1.5 million inhabitants in western Sweden. Methods The economic burden of stroke was estimated from a societal perspective with an incidence approach. Data were collected from clinical registries and 3,074 patients were included. In the cost calculations, both direct and indirect costs were estimated and were based on costs for 12 months after a first-ever stroke. Results The total excess costs in the first 12 months after the first-ever stroke for a population of 1.5 million was 629 million SEK (€69 million). Men consumed more acute care in hospitals, whereas women consumed more rehabilitation and long-term care provided by the municipalities. Younger patients brought a significantly higher burden on society compared with older patients due to the loss of productivity and the increased use of resources in health care. Conclusions The results of this cost-of-illness study were based on an improved calculation process in a number of fields and are consistent with previous studies. In essence, 50% of costs for stroke care fall on acute care hospital, 40% on rehabilitation and long-time care and informal care and productivity loss explains 10% of total cost for the stroke disease. The result of this study can be used for further development of the methods for economic analyses as well as for analysis of improvements and investments in health care.